2015
DOI: 10.1080/09540121.2015.1090538
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the unmatched count technique and direct self-report for sensitive health-risk behaviors in HIV+ adults

Abstract: Researchers often rely on self-report measures to assess sensitive health-risk behaviors in HIV+ individuals, yet the accuracy of self-report has been questioned, particularly when inquiring about behaviors that may be embarrassing, risky, and/or taboo. We compared an anonymous reporting method—the Unmatched Count Technique (UCT)—to direct self-report in order to assess reporting differences for several health-risk behaviors related to medication adherence and sexual risk. Contrary to hypotheses, the UCT only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(12 reference statements)
2
6
0
Order By: Relevance
“…In our study, LR responses neither corresponded strongly with known actual answers with regard to HIV status and HIV testing refusal, nor were closer to known actual answers than standard direct questionnaires. Our results agree with recent findings from A Arentoft, et al [ 13 ], which similarly did not find that list randomization improved estimates over direct questioning. The failure of our implementation of LR to improve elicitation of sensitive information in surveys highlights the inherent complexity of this and other related methods, suggesting that researchers should be cautious when using them in the field.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, LR responses neither corresponded strongly with known actual answers with regard to HIV status and HIV testing refusal, nor were closer to known actual answers than standard direct questionnaires. Our results agree with recent findings from A Arentoft, et al [ 13 ], which similarly did not find that list randomization improved estimates over direct questioning. The failure of our implementation of LR to improve elicitation of sensitive information in surveys highlights the inherent complexity of this and other related methods, suggesting that researchers should be cautious when using them in the field.…”
Section: Discussionsupporting
confidence: 93%
“…There is limited evidence of whether LR improves self-reported elicitation of sensitive behaviors with validation against known truths in public health, with mixed results [ 10 13 ]. In HIV, A Arentoft, et al [ 13 ] found that LR yielded lower estimates of negatively stigmatized behaviors in HIV+ patients compared with directly asked questions, counter to their initial hypothesis. While this study used a proxy for known truth by directly observing adherence data after the survey was completed, they did not directly observe the retrospective adherence behavior asked about in the survey.…”
Section: Introductionmentioning
confidence: 99%
“…However, the other two methodologies are increasingly different from this straighrorward assessment. One uses the unmatched count technique, an indirect es4mate aimed at reducing social desirability response bias (Arentol et al, 2016) (see Method for details). The second generates an indirect es4mate of the popula4on size of QRP users by using social network informa4on from the general popula4on of psychologists (Jing et al, 2014;McCormick et al, 2010;Salganik et al, 2011;Zheng et al, 2006).…”
mentioning
confidence: 99%
“…For this reason, two other estimating methods will be used. One is the unmatched count technique, an indirect estimate aimed to reduce social desirability bias by removing the requirement for participants to identify as QRP users to the researchers (Arentoft et al, 2016). The second estimator generates an indirect estimate of QRP use by using social network information from the general population of psychologists (Jing, Qu, Yu, Wang, & Cui, 2014;Zhang et al, 2010;Zheng, Salganik, & Gelman, 2006).…”
Section: Prevalencementioning
confidence: 99%